Implementation of pharmaceutical preparation management during the covid-19 pandemic: literature review - Maharani Dwi Pratiwi; Abdul Rahem; Liza Pristianty (Science Midwifery, 2023)
Pharmacists should face challenging situations such as in the pandemic. The main problem is the preparation management of the drugs. Thus, this study aims to find out the effects of the pandemic on the management of pharmaceutical preparations. Articles were searched for using the PubMed and ScienceDirect search engines. PRISMA, or Preferred Reporting Items for Systematic Reviews and Meta-Analyzes, was utilized in this study. The data selection flow used the PICO (Population, Intervention, Compare, Outcome) method. Based on the discussion conducted, the management of pharmaceutical preparations in pharmacies during the COVID-19 pandemic can still be implemented with imperfect outcomes.